Utilización del sistema operativo ubuntu como recurso didáctico para la enseñanza aprendizaje en la asignatura informática para los estudiantes del primer año de bachillerato del Colegio Particular Mixto Eloy Alfaro de la ciudad de Machala periodo 2013-2014. - Chávez Porras, Angelo Darío (2013)
This thesis aims to be a tool of learning for students in the Special Education Unit Eloy Alfaro city of Machala for which the authors of this thesis we used the technological, human and financial resources that best suit the needs of the school, so we can instruct our knowledge institutions and even the future leaders of our country the same technology tools that will help much in your personal life and your professional life.